Lay piety and religious discipline in Middle English literature - Rice, Nicole R., 1973- (Cambridge University Press, 2008)
An examination of spiritual discipline, religious identity, and orthodoxy in Langland and Chaucer.
Keywords: English prose literature -- Middle English, 1100-1500 -- History and criticism.; English poetry -- Middle English, 1100-1500 -- History and criticism.; Religion and literature -- England -- History -- To 1500.; Spiritual life in literature.; Spiritual life -- Christianity -- History of doctrines -- Middle Ages, 600-1500.; Religious thought -- Middle Ages, 600-1500.; Prose anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique.; Poésie anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique.; Vie spirituelle dans la littérature.; Pensée religieuse -- 600-1500 (Moyen Âge); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; English poetry -- Middle English; English prose literature -- Middle English; Religion and literature; Religious thought -- Middle Ages; Spiritual life -- Christianity -- History of doctrines -- Middle Ages; Spiritual life in literature; England; Mittelenglisch; Literatur; Religiöses Leben; Frömmigkeit; Disziplin; To 1500; Criticism, interpretation, etc.; History